Equine hepacivirus (EqHV) phylogeny, infectivity profile and entry in Thoroughbred racehorses - Akagha, Terry (2021)
Hepatitis C virus (HCV) causes chronic and acute liver diseases in humans. This virus’s origin is unknown, and many research works into the design of a prophylactic vaccine have been inhibited due to the lack of a tractable model, partly due to its narrow host range (humans and chimpanzees). Equine Hepacivirus (EqHV) in 2011 was discovered in respiratory samples of dogs and found to be the closest genetic relative to Hepatitis C virus (HCV). This virus naturally infects horses and has several similarities to HCV, ranging from delayed onset of seroconversion, persistent infection, and liver pathology, thereby making it a potential experimental model to study hepacivirus infections in their natural host.